2014
DOI: 10.5152/tud.2014.09735
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of radical cystectomy in elderly patients

Abstract: We found that oncological outcomes of radical cystectomy performed with the indication of bladder tumor were comparable between young and elderly. We believe that age per se should not constitute a contraindication for radical cystectomy operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
2
4
0
Order By: Relevance
“…[6] mentioned that the complete response rates in patients receiving multimodal treatment have ranged from 47% to 87%, and 5-year overall survival rates have ranged from 30% to 70% in different studies. These outcomes are almost similar with the present report by Görgel et al; [1] who reported the 5-year overall survival rates 43.9% vs. 45.9% with RC for patients over and under 70 years of age, respectively.…”
Section: The Role Of Bladder Preservation In This Group Of Patientssupporting
confidence: 93%
“…[6] mentioned that the complete response rates in patients receiving multimodal treatment have ranged from 47% to 87%, and 5-year overall survival rates have ranged from 30% to 70% in different studies. These outcomes are almost similar with the present report by Görgel et al; [1] who reported the 5-year overall survival rates 43.9% vs. 45.9% with RC for patients over and under 70 years of age, respectively.…”
Section: The Role Of Bladder Preservation In This Group Of Patientssupporting
confidence: 93%
“…17 , 18 Similar age threshold was adopted in a study of Görgel et al which evaluated the outcomes of RC among elderly patients in Turkey. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Similar with RCC surgery, a recent study from Turkey found that oncological outcomes of radical cystectomy were comparable between young and elderly patients (cut-off value 70 years of age) and age should not constitute a contraindication for radical cystectomy operations. 29 The first limitation of the current study is being a single-center experience and its retro-spective design. Secondly, the sample size of the groups is relatively small.…”
Section: Discussionmentioning
confidence: 97%